THE EFFECT OF NITROGEN FERTILIZATION AND CUTTING HEIGHT ON THE DRY MATTER PERCENTAGE AND QUALITY OF WHITE CORN CROP SORGHUM BICOLOR L. (British Journal of Global Ecology and Sustainable Development, 2023)
A field experiment was conducted during the spring season 2021-2022 in the field of the College of Agriculture, University of Basra / Karmat Ali site (latitude 30°.57 north and longitude 47°.80) in order to study the effect of five levels of nitrogen fertilizer (0, 150, 200, 250 and 300) kg N ha-1 and three levels of cutting height (10, 20 and 30) cm in the percentage of dry matter and its quality for the white corn crop Sorghum bicolor L. In a mixture of alluvial soil, as planting took place on 1/4/2022, the experiment was applied according to the method Factorial experiments using the randomized complete block design (R.C.B.D) with three replications. The different factorial coefficients were distributed to the workers randomly within each sector. Three bunches of crop were taken and the following characteristics were measured for each bunch: percentage of dry matter and percentage of protein in the plant, percentage of fiber in the plant, the results showed The level of nitrogen fertilizer was superior to 250 kg N ha-1 , which recorded the highest average percentage of protein in the plant, which reached 13.26, 12.08, and 9.24 %, and the highest average dry matter percentage reached 25.98, 28.67, and 28.23 % for the three weeds, while the relationship between the protein percentage and the fiber percentage was inversely By increasing the percentage of protein in the plant, the percentage of fiber in the plant decreases. The results also showed that the cutting height of 10 cm recorded the highest average percentage of protein in the plant, which reached 10.71, 9.46, and 7.71% for the three cuttings, respectively, and the highest average percentage of dry matter in the plant reached 28.15 % in the second cutting. While the effect of the interaction between nitrogen fertilization and cutting height was significant, as the overlap treatment of 250 kg N ha-1 with a cutting height of 10 cm recorded the highest average percentage of protein in the plant amounted to 14.38 and 10.21% for the first and second cuttings, and the highest average percentage of dry matter reached 28.93% for the cuttings. the second.